2 - From Collective Leadership to Presidentialism: I.B. Tabata, Authorship and the Biographic Threshold - Ciraj Rassool, (Afrika Zamani, 2022)
This article goes beyond merely drawing on the archive to plot a narrative of South African resistance leader I. B. Tabata's biography as a means of under- standing identity issues about the individual, political movement and the na- tion. It is part of a larger project that tries to push political biography beyond modernist documentary methods and social history frames of individual and social context. It focuses on authorship and writing as one of the circumstances out of which the idea emerged of I. B. Tabata as a leader with a biography as the narrative of a great leader of a liberation movement. It attempts to historicize Tabata's biography, which can be understood as having undergone a transition from biographic denial and a stress on collective leadership to biographic narra- tion under conditions of repression. This process culminated in the embracing of biography as an element of a politics of presidentialism.